Manajemen Public Relations Indonesian Flag Football Association - Nurunnisa Nabilla Azhary; Dadan Mulyana (Bandung Conference Series: Public Relations, 2022)
Abstract. The Covid-19 pandemic has had a negative impact on the field of flag football, due to the limited space for team sports activities in open spaces. With these limitations, the Bandung Regional Indonesian Flag Football Association (IFFA) is still able to carry out its routine activities until it successfully organizes various events. Behind the success of the event during the current pandemic, it cannot be separated from the management of public relations and the communication process carried out by the Bandung Regional IFFA administrators with their stakeholders. This study focuses on how the management of PR IFFA Regional Bandung in increasing existence through the "West Conference Mini Tournament" event during the pandemic. The purpose of this study was to determine the process of fact finding, planning, communication, and evaluation of the Bandung Regional IFFA PR management in the "West Conference Mini Tournament" event. This study uses a qualitative research method with a case study approach. The sources of data used are interviews, observations, literature studies and online data searches. The results show that the fact finding process of IFFA Regional Bandung is to create event innovations, create issues on social media and conduct a survey of flag football players. The planning stage of IFFA Regional Bandung is to design a strategy, determine goals to plan the implementation of health protocols. The communication stage is the implementation of the strategy that has been designed, including the internal and external communication processes. At the evaluation stage, there are obstacles, supporting factors and impacts obtained from the "West Conference Mini Tournament" event. Abstrak. Pandemi Covid-19 memberikan dampak buruk pada bidang olahraga flag football, karena terbatasnya ruang untuk melakukan aktivitas olahraga beregu di ruang terbuka. Dalam keterbatasannya tersebut, Indonesian Flag Football Association (IFFA) Regional Bandung tetap mampu menjalankan aktivitas rutinnya hingga berhasil menyelenggarakan berbagai event. Dibalik keberhasilan event di masa pandemi seperti sekarang tidak terlepas dari manajemen public relations dan proses komunikasi yang dijalankan oleh para pengurus IFFA Regional Bandung dengan stakeholdersnya. Penelitian ini memiliki fokus penelitian bagaimana manajemen PR IFFA Regional Bandung dalam meningkatkan eksistensi melalui event “West Conference Mini Tournament” di masa pandemi. Tujuan penelitian ini adalah untuk mengetahui proses fact finding, planning, communication, dan evaluation manajemen PR IFFA Regional Bandung dalam event “West Conference Mini Tournament”. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus. Adapun sumber data yang digunakan berasal dari wawancara, observasi, studi kepustakaan dan penelusuran data online. Hasil penelitian menunjukkan bahwa proses fact finding IFFA Regional Bandung adalah membuat inovasi event, membuat isu di social media dan melakukan survey terhadap para pemain flag football. Tahap planning IFFA Regional Bandung yaitu merancang strategi, menentukan tujuan hingga merencanakan pelaksanaan protokol kesehatan. Tahap communication yaitu pengimplementasian strategi yang sudah dirancang, meliputi proses komunikasi internal dan eksternal. Pada tahap evaluation, terdapat hambatan, faktor pendukung dan dampak yang didapat dari penyelenggaraan event “West Conference Mini Tournament”.